Interaction of Conditional Incentives for Ecosystem Conservation with Tenure Security: Multiple Roles for Tenure Interventions - Monterroso, I.; Sills, E.O. (Springer, 2022)
This chapter examines the role of tenure in conditional incentives for ecosystem conservation, often known as PES or payment for ecosystem services. PES systems that mimic market exchange require that resource tenure be clear and uncontested. In practice, there are different levels of conditionality in PES and different types of tenure challenges. REDD+, or Reducing Emissions from Deforestation and Forest Degradation, was initially conceived as a PES system embedded in a global exchange of carbon credits, thus requiring secure forest tenure. We examine one global initiative to achieve that, the Dedicated Grant Mechanism for Indigenous Peoples and Local Communities. Cases in Peru and Indonesia illustrate how tenure interventions can both enable implementation of conditional incentives and become part of those incentives.